Pembelajaran Saintifik Dalam Peningkatan Motivasi Belajar Pai Di SMK Negeri Mojoagung Jombang - Abd. Rozaq; Umi Habibah (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2021)
This study describes the application of scientific learning in Islamic education subjects at SMK Negeri Mojoagung. This research uses a qualitative approach. Data collection methods: observation, interviews and documentation. The data analysis technique uses the interactive model of Miles and Huberman which includes data reduction, data presentation and conclusion drawing. To check the validity of the data, it was used research extension, observation persistence and triangulation. The result of the research is that scientific learning in Islamic Education subjects at SMK N Mojoagung is applied through student learning activities as follows: Observing (seeing pictures, reading, listening to and identifying the reading of the Koran, listening to explanations, observing the benefits and lessons of wisdom), asking questions (teacher asking students, students asking the teacher, students asking students), trying (memorizing the arguments of the Qur'an, looking for benefits and wisdom, digging information about the consequences of an action, looking for arguments from the Al-Qur'an or hadith from other sources ), reasoning (making conclusions about the benefits and wisdom of orders or prohibitions, making conclusions on matters relating to the impact of doing an action), communicating (expressing opinions, presenting the results of conclusions orally or in writing and responding to a friend's presentation).